Wireless sensor network platform for monitoring the industrial apparatus - Bhautik Patil; Supriya Mahajan; Pratiksha Sawarkar (International Journal of Innovations in Engineering Research and Technology, 2021)
Wireless Sensor Networks (WSNs) are one of the fastest growing and emerging technologies in the field ofWireless networking. WSNs have a vast amount of applications including environmental monitoring, oil andgas, agriculture, inventory control, robotics and health care. This paper focuses on monitoring and protectionof oil and water operations using WSNs that are optimized to decrease installation, and maintenance cost,energy requirements, increase reliability and improve communication efficiency. Such model could providenew tools for research in predictive maintenance and condition-based monitoring of factory machinery ingeneral and for open architecture machining system in particular.